New perspectives on education - Latorre Ariño, Marino (2016)
If we analyze the demands of the university and the school until a few years ago, the university student was asked to acquire a series of knowledge of the specialty (most of them theoretical) to become a good professional. I learned the practice soon when I arrived at the company and at work, because I had a solid theoretical background. At the beginning of the 21st century, skills learning is required. The competences are complex skills-abilities that refer to the management of knowledge, skills (abilities-skills) and attitudes (values), in the realization of specific actions of a profession and with approved quality standards. The core of a competition is a capacity or potential that a person has to perform certain actions with accepted quality standards.